EMBR-09. EXAMINING THE ROLE OF THE DEVELOPMENTALLY ENCODED TRANSCRIPTION FACTOR, LHX9, IN GROUP 3 MEDULLOBLASTOMA. (1st June 2021) - Injac, Sarah; Rivas, Bryan; Arabzade, Amir; Zhao, Yanhau; Parsons, D William; Mack, Stephen
Abstract: Medulloblastoma (MB) is the most common malignant brain tumor of childhood. Despite major advances in our understanding of the biology of MB, novel treatments remain urgently needed. Using a chemical-genomics driven drug repositioning strategy, we identified the cardiac glycoside family of compounds as potential treatments for Group 3 MB. We subsequently demonstrated that single-agent treatment with digoxin prolongs survival in a patient-derived xenograft model (PDOX) of Group 3 MB to a degree comparable to radiation therapy, a mainstay in the treatment of MB. Finally, we examined the mechanism of digoxin-mediated cell killing using RNA-seq. This work identified LHX9, a member of the LIM homeobox family of transcription factors, as the gene most significantly down-regulated following treatment (Huang and Injac et al, Sci Trans Medicine, 2018). Homologs of LHX9 play key roles in cerebellar development via spatially and temporally restricted expression and LHX9 has been proposed as a core transcription factor (TF) in the regulatory circuitry of Group 3 tumors. Loss of function of other core TFs has been shown to impact MB growth. The role of LHX9 in MB, however, has not been previously experimentally evaluated. We now report that knockdown of LHX9 in MB-derived cell lines results in marked growth inhibition. RNA-seq analysis of LHX9-depleted cells showed changes which included alterations in extracellular matrix-receptor interactions and TGFb signaling. These findings raise the possibility that loss of LHX9 plays a major role in digoxin-mediated cell killing and that LHX9 represents a key dependency required for the growth of Group 3 MB. Clinical targeting of core TFs would represent a novel approach to targeting this devastating disease.